The Bourgeois: Between History and Literature (an excerpt) - Franco Moretti (Journal of Economic Sociology, 2014)
The book “The Bourgeois: Between History and Literature” written by Franco Moretti, the professor in the Humanities at Stanford University and the founder of the Center for the Study of the Novel and Literary Lab, is devoted to the history of the bourgeois as a social class of the modern Western society. The bourgeois, refracted through the prism of literature, is the subject of “The Bourgeois”. Addressing to some pieces of the Western literature, the author tries to scrutinize reasons of the bourgeois culture’s golden age and to reveal causes of its further fall. Moretti focuses not on real relationships between social groups but on legitimate cultural forms, which demonstrate peculiarities of the bourgeois and demarcate it from working and ruling classes. In addition, the author seeks an answer to the questions why the notion of bourgeois was being replaced with the concept of the middle class and why the bourgeois failed to resist political and cultural challenges of the modern Western society.The journal of Economic Sociology publishes “Introduction: Concepts and Contradictions” from “The Bourgeois”. In the Introduction, Moretti formulates the problem of the study, defines key concepts and explains the applied methodology, demonstrating weaknesses and strengths of the formal analysis of literary prose for understanding the social history. In the Introduction, Moretti describes the book’s structure and sheds lights on the dark corners, which require additional research.